Transformasi Arsitektur Pasar Johar Semarang : Pra-Pasca Kebakaran - R.A. Sunia Widiaswara; Jonathan Hans Yoas Sihotang; Indri Astrina Wirakusumah (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study discusses the architectural transformation of Pasar Johar Semarang before and after the major fire incident in 2015. Designed by architect Thomas Karsten, Pasar Johar holds significant historical and architectural values. The fire prompted a comprehensive revitalization of the market’s environment, site, and building while maintaining its original character. This research employs an architectural anatomy approach covering three main scopes: environment, site, and building, and uses a qualitative descriptive-analytical method through four stages: (1) documenting conditions before and after the fire, (2) classifying architectural elements, (3) comparing visual and structural transformations, and (4) drawing conclusions based on the analysis to evaluate the extent of the transformation. The results show that the revitalization made the area more organized, functional, and sustainable. Distinctive structures such as mushroom columns and drainage systems were preserved, while zoning and public spaces were reorganized to improve efficiency and comfort. This restoration not only improved physical aspects but also strengthened the market’s social function as a community interaction space. Pasar Johar now serves as an example of a traditional market that can adapt to modern urban challenges without losing its architectural identity and its potential as a sustainable economic and social hub.